Maximizing Corporate Value through Mergers and Acquisitions : a Strategic Growth Guide - Gaughan, Patrick A. (New York : Wiley, 2013)
Solid guidance for selecting the correct strategic basis for mergers and acquisitions Examining how M & A fits in corporate growth strategies, Maximizing Corporate Value through Mergers and Acquisitions covers the various strategic reasons for companies entering mergers and acquisitions (M & A), with a look at those that are based on sound strategy, and those that are not. Helps companies decide whether M & As should be used for growth and increased corporate valueExplores why M & A deals often fail to deliver what their proponents have represented they wouldEx.
Empirical Evidence on the Acquisition Programs of the 1960sHow Likely Is It That Diversifying Acquisitions Will End Up Being Sold Off?; Is There a Diversification Discount?; Focus Hypothesis; Types of Focus Increases; Focus-Increasing Asset Sales Raise Value; Explanation for the Diversification Discount; Related versus Unrelated Diversification; Why Are Very Diversified Companies Allowed to Form? Beware of the Empire Builders; Do Managerial Agendas Drive M & A?; Notes; Chapter 5: Horizontal Integration and M & A; Advantages of Holding the One and Two Position in the Industry.
Benefits of Size: Spotlight on the Mobile Telecommunications Industry.
Includes bibliographical references and index.
Print version record.
Keywords: Consolidation and merger of corporations; International business enterprises -- Management; Strategic planning; BUSINESS & ECONOMICS -- Mergers & Acquisitions; BUSINESS & ECONOMICS -- International -- Accounting; Consolidation and merger of corporations; Electronic books